Effect of Lime Juice on the Properties of Used Cooking Oil in Biodiesel Degumming Process - Handoko, Riki; Saragih, Yessy Dea Sylvia (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
The purpose of this study is to determine the effectiveness of lime juice on the characteristics of used cooking oil in the degumming process in terms of free fatty acid (FFA) and acid number. The specific objective of the author is to determine the limits of the ability of lime juice as an organic catalyst in the degumming process. The data are obtained by carrying out descriptive experiments on used cooking oil processed by degumming method with lime juice (Citrus aurantiifolia Swingle) as organic catalyst and studied the characteristics of FFA and acid number with SNI 7182: 2015 standard with volume variations of 1%, 2%, 3%. The research process was conducted at the Integrated Laboratory of the University of North Sumatra, which obtained the best results at 2% lime juice content with FFA value of 1.87% and acid number of 2.66 mgKOH/g. Degumming with lime juice is not effective in reducing the FFA content and acid number.